KASTORIA “BLIND” ACTIVE FAULT: HAZARDOUS SEISMOGENIC FAULT OF THE NW GREECE - Metaxas, Ch. P.; Lalechos, N.S.; Lalechos, S.N. (Bulletin of the Geological Society of Greece, 2010)
The Aliakmon river bed, as well as a series of certain parallel narrow grabens, striking NW-SE are filled with Neogene-Quaternary deposits; thus showing the existence of the covered, “blind”, fault zone, which borders the Eastern edge of Meso-Hellenic Trench and passes in close vicinity to the Kastoria town. Distribution of earthquakes epicentres (M≥4.0, for the period of 1930-2009) along this segmented rupture zone, proves the existence at depth of an active seismogenic fault which has generated some strong earthquakes in the past: 1709, M = 6.0; 1812, M = 6.5 and 1894, M = 6.1 (~ 100-year Recurrence Time events). The calculations of Lapsed Rate characterizing the stage of the fault seismic cycle (LR = 115%) show that the active Kastoria fault could be in a pre-seismic stage of its seismic cycle. Applying the seismicity rates model (time-independent Gutenberg-Richter recurrence model) and using the fault seismicity parameters, obtained inside the fault influence zone, as input in EZ-FRISK® software, the Probabilistic Seismic Hazard Analysis has been carried out for the area of Kastoria town. The results show that calculated magnitude for event with 100- year recurrence time is ~6.1, which correspond to the magnitude of three events, occurred at the fault during the last 300 years (corresponding average slip rate . 3 mm/year). As the calculated Hazard Curve shows, the event of that range could give ground shaking in the Kastoria town in the order of 0.625 g at the spectral period of 0.3 sec.